PRESERVICE TEACHERS ON TEACHING WITH AND ABOUT ICT: AN INDONESIAN STUDY - Relmasira, Stefanus Christian; Thrupp, Rose-Marie (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2016)
Teaching about and with digital technologies continues to challenge teachers. Aligned with the permeation of Information Communication Technologies (ICT) in our daily lives is the challenge of ICT in the classroom. Curriculum writers strive to identify declarative and procedural knowledge needed by future citizens. Teachers strive to design ICT-enabled learning that engages contemporary learners.Â  The identity of a teacher of ICT and using ICT for learning challenges preservice teachers as they create their own identity in the classroom.Â  These challenges cross borders, both geographical and cultural. Using a research approach developed by Hunt (2015), preservice teachers in a teacher education program in Central Java, Indonesia were asked to draw what teachers and ICT look like, sound like, and feel like. This study builds upon the ideas of Goodenough (1926) and Chambers (1983) to examine the views of teachers and ICT held by preservice teachers. These findings can inform the design of teacher education programs in supporting preservice teachers to build their self-efficacy as teachers teaching with and about ICT in their classroom and contribute to the construction of professional learning post-graduation.